Physically based rendering from theory to implementation - Pharr, Matt (Morgan Kaufmann Elsevier Science [distributor], 2010)
Physically Based Rendering, 2nd Edition describes both the mathematical theory behind a modern photorealistic rendering system as well as its practical implementation. A method - known as 'literate programming'- combines human-readable documentation and source code into a single reference that is specifically designed to aid comprehension. The result is a stunning achievement in graphics education. Through the ideas and software in this book, you will learn to design and employ a full-featured rendering system for creating stunning imagery. New sections on subsurface scattering, Metropolis light transport, precomputed light transport, multispectral rendering, and much more. Includes a companion site complete with source code for the rendering system described in the book, with support for Windows, OS X, and Linux
Includes bibliographical references and index
Keywords: COMPUTERS / Image Processing; PHOTOGRAPHY / Techniques / Digital; TECHNOLOGY & ENGINEERING / Imaging Systems; COMPUTERS / Digital Media / Graphics Applications; Computer graphics; Three-dimensional display systems; Datorgrafik; Tredimensionella bilder; Metamathematik; Realistische Computergrafik; Dreidimensionale Computergrafik; Softwareentwicklung; Rendering; Geometrische Modellierung; Computergrafik